Modulation of ERCC1-XPF Heterodimerization Inhibition via Structural Modification of Small Molecule Inhibitor Side-Chains - Weilbeer, Claudia; Jay, David; Donnelly, James C.; Gentile, Francesco; Karimi-Busheri, Feridoun; Yang, Xiaoyan; Mani, Rajam S.; Yu, Yaping; Elmenoufy, Ahmed H.; Barakat, Khaled H.; Tuszynski, Jack A.; Weinfeld, Michael; et al. (Frontiers in Oncology, 2022)
Inhibition of DNA repair enzymes is an attractive target for increasing the efficacy of DNA damaging chemotherapies. The ERCC1-XPF heterodimer is a key endonuclease in numerous single and double strand break repair processes, and inhibition of the heterodimerization has previously been shown to sensitize cancer cells to DNA damage. In this work, the previously reported ERCC1-XPF inhibitor 4 was used as the starting point for an in silico study of further modifications of the piperazine side-chain. A selection of the best scoring hits from the in silico screen were synthesized using a late stage functionalization strategy which should allow for further iterations of this class of inhibitors to be readily synthesized. Of the synthesized compounds, compound 6 performed the best in the in vitro fluorescence based endonuclease assay. The success of compound 6 in inhibiting ERCC1-XPF endonuclease activity in vitro translated well to cell-based assays investigating the inhibition of nucleotide excision repair and disruption of heterodimerization. Subsequently compound 6 was shown to sensitize HCT-116 cancer cells to treatment with UVC, cyclophosphamide, and ionizing radiation. This work serves as an important step towards the synergistic use of DNA repair inhibitors with chemotherapeutic drugs.